Inter‐Individual Variation in Postprandial Glycemic Responses in Women Co‐Ingesting Green Leafy Vegetables with a Carbohydrate Meal: Interactions with the Sirtuin System. Issue 13 (7th June 2021) - Sayegh, Marietta; Henderson, Jaye; Farquharson, Andrew J.; Horgan, Graham; Ranawana, Viren; Drew, Janice E.
Abstract : Scope: Green leafy vegetables (GLV) may improve postprandial glycemic responses (PGR) and metabolic health. However, inter‐individual variations (IIV) preclude conclusive evidence. Sirtuin system is emerging as a key player in blood glucose control. This study investigates IIV in PGR in women co‐ingesting GLV with a carbohydrate meal and interactions with the sirtuin system. Methods and Results: Volunteers ( n = 31 women) consume rice, rice with bok choy, or spinach (75g available carbohydrate) on separate occasions. Postprandial glucose, insulin, adropin, and lipid levels are measured. Anthropometric measurements and sex hormones are measured. GeXP assay measures whole blood postprandial gene expression profiles of 25 markers involved in sirtuin signaling. GLV consumption has no significant effect on PGR, which shows high variation. PGR correlated with age, but no other consistent associations are observed. Sirtuin gene expression profiles reveal distinct stratified subgroups associated with PGR, lipid, insulin, fat mass, waist/hip circumferences, and adropin levels. Conclusion: PGR to co‐ingesting GLV with a carbohydrate meal are highly variable in this cohort and fail to reveal a significant reduction in PGR. Variable responses are largely independent of menopausal status and meal consumed. However, lower expression of sirtuin gene targets is associated with higher PGR and with markers linked to health status. Abstract : Women consuming rice with and without bok choy or spinach exhibit variable increases in blood glucose post‐consumption, which is not consistently associated with the meal consumed. However, measurement of blood markers indicates that higher post meal blood glucose is associated with lower levels of sirtuin gene expression measured in blood. The sirtuin system regulates blood glucose to maintain metabolic health.